PENERAPAN PENDEKATAN MODEL WATERFALL DALAM PENGEMBANGAN SISTEM E-RAPOR - Langgeng Hadi Prasetijo; Firdiyan Syah; Sapta Hary Surya Wibowo; Fajar Ardanu; Suyadi -; Emma Utami (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2016)
Information system development project can be seen as the life cycle (Systems Development Life Cycle / SDLC) which in practice can be done using different approaches. Waterfall is one of method that is often applied in the SDLC. This paper discusses the application of the Waterfall model in the E-Score Card system development project in high school report card as a follow-up to the minister Instruction No. 2 of 2011 on Education Data Management Activities and Permendikbud No. 53 of 2015 on the Assessment of Learning Outcomes. E-Score Card system was developed on the grounds that information management learning and assessment of learning outcomes that involve many data items, has a high complexity, and no fault tolerance for critical data related to many parties, so that the necessary existence of a computer based system. In addition, the E-Score Card system is also necessary to standardize, facilitate the education unit, and facilitate government monitoring information management learning and assessment of learning outcomes. Referring to the approach of the Waterfall model, the E-Score Card system is developed through four stages, namely planning, analysis, design, and implementation. Logical Model of E-Score Card system involving four external entities, namely Admin, Guardian Class, Teachers, and Students. E-Score Card system has four main processes, namely by Admin master data management, data transactions management by the Guardian Class and the Master, as well as display information of value to students. Prototype System E-Report Card was developed using the programming language PHP 5, MySQL DBMS, OS MSWindows, and web server Xampp 1.7.2.